2007
DOI: 10.1111/j.1463-6409.2007.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of pontobdelline leeches and their place in the descent of fish leeches (Hirudinea, Piscicolidae)

Abstract: Molecular phylogeny of pontobdelline leeches and their place in the descent of fish leeches (Hirudinea, Piscicolidae). -Zoologica Scripta, 36 , 271-280.Phylogenetic relationships of all genera of the fish leech subfamily Pontobdellinae were investigated using mitochondrial (12S rDNA, COI, tRNA-Leu, ND1) and nuclear (28S rDNA) DNA sequences under maximum likelihood, Bayesian inference and parsimony. All methods resulted in trees that corroborated the monophyly of the family Piscicolidae, but recovered their sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Phylogenetic analyses demonstrated that both the tribe Platybdellini and the subfamily Platybdellinae (piscicolid leeches with no pulsatile vesicles) are not monophyletic groups (Williams & Burreson 2006;Utevsky et al, 2007). Admittedly, the information on the reproductive system and other internal organs seems not to be enough to determine phylogenetic affinities of Ceratobdella.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Phylogenetic analyses demonstrated that both the tribe Platybdellini and the subfamily Platybdellinae (piscicolid leeches with no pulsatile vesicles) are not monophyletic groups (Williams & Burreson 2006;Utevsky et al, 2007). Admittedly, the information on the reproductive system and other internal organs seems not to be enough to determine phylogenetic affinities of Ceratobdella.…”
Section: Discussionmentioning
confidence: 89%
“…The tribe Platybdellini includes seven genera: Platybdella Malm, 1863, Cryobdella Harding, 1922, Heptacyclus Vasilyev, 1939, Malmiana Strand, 1942, Oceanobdella Caballero, 1956, Sanguinotus de Silva & Burdon-Jones, 1961and Arctobdella de Silva & Kabata, 1961 Malmiana is now considered a junior synonym of Heptacyclus (see Williams & Burreson, 2006). The boreal genera Platybdella, Heptacyclus and Oceanobdella possess a number of morphological, biogeographical and phylogenetic affinities (Utevsky, 2003;Utevsky & Trontelj, 2004;Williams & Burreson, 2006;Utevsky et al 2007). In contrast to Ceratobdella, species of Heptacyclus and Oceanobdella have eyes and usually these leeches are wellpigmented or have a colouration pattern on the body.…”
Section: Discussionmentioning
confidence: 98%
“…This species has been already employed in several molecular phylogenetic analyses under the name of Oceanobdella sp. (Utevsky and Trontelj 2004, Williams and Burreson 2006, Utevsky et al 2007) and its morphological description is presented herein.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the new molecular studies have raised doubts on the monophyly of the Platybdellinae and Piscicolinae, and implied that Pontobdellinae could be paraphyletic (Williams & Burreson 2006). Recently, the Pontobdellinae have been described also as polyphyletic (Utevsky et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The existing division to 18 tribes and 52 genera Epshtein 2004) in the latest morphological and molecular studies have been examined (Siddall et al 2001;Utevsky & Trontelj 2004). Moreover, some of the latest molecular studies questioned the previous division of Piscicolidae into 18 tribes (Utevsky et al 2007;Williams & Burreson 2006). What is more, the new molecular studies have raised doubts on the monophyly of the Platybdellinae and Piscicolinae, and implied that Pontobdellinae could be paraphyletic (Williams & Burreson 2006).…”
Section: Introductionmentioning
confidence: 99%